Synthesis of new metal complexes derived from 5-nitroso 8-hydroxy quinoline and Salicylidene P-imino acetophenone with Fe(II), Co(II), Ni(II) and Cu(II) ions - Rasheed, Rashed Taleb (Al-Nahrain Journal of Science, 2018)
Bidentate Schiff-bases have been among those that are extensively used in preparing metal complexes. These ligands are described according to their donor set N, N-donor and N, O- donor Schiff-bases. Bidentate schiff base having nitrogen and oxygen atom was prepared by condensation of the P-amino-acetophenone with salicylaldehyde in absolute ethanol. An ethanol solution of Schiff base and an ethanol solution of 5- nitroso 8-hydroxy- quinoline were reacted with aqueous solution of metal salts to give complexes with the general formula [M(L)(Q)], where Q = 5- nitroso 8-hydroxyquinoline, L = (salicylaldehyde + p-amino-actophenone) and MII = Fe, Co, Ni and Cu ions. The resulting products were found to be solids which were characterized using FTIR and UV-Vis spectroscopy. An elemental analysis was performed using atomic absorption technique; magnetic susceptibility and the conductivity were also measured.